Nomadism in the arid zone of Eurasia. Myths and reality - T. S. Zhumaganbetov (Nomadic Civilization: Historical Research, 2023)
This article is devoted to the main problems of nomadism and nomadic societies. The author of the proposed article proposes to abandon the old traditional conceptual apparatus based on the characterizing term “nomadic”. Studies of modern foreign and Kazakh historians and ethnologists on nomadic civilization and nomadism have shown that there are much more stationary settled population in the arid zone of Eurasia than those groups that had the opportunity for seasonal movements. The categories of “nomadism” and “pasture” include full-fledged sectors of the economy: crop production, gardening, crafts, fishing, trade, employment in management, etc. The author comes to the conclusion that the steppe civilization is characterized by features that determine its deep essence. This is, first of all, pastoral animal husbandry with a combination of settled life of the nomadic population; the presence of a society in the arid zone, united by economic interests; an organized migration process with a sustainable route; the diverse nature of relations in the sphere of land ownership; observance of ecological balance between society and the environment; the formation in nomadism of a supra-communal, centralized power capable of generating various forms of state power; the predominance of tribal ownership of pastures and on the path of seasonal movements; the limited nature of class exploitation and, finally, the dominance of grazing in the economic life of a nomadic society.